Enfrentamentos político-pedagógicos no Pacto Nacional pela Alfabetização na Idade Certa (PNAIC): desafios de alfabetizar letrando - Freitas, Mirella de Oliveira (2020)
This work is part of the Applied Linguistics’ field and aims to investigate the didacticmethodological proposals of the Pacto Nacional pela Alfabetização na Idade Certa (PNAIC), an official program of continuing teacher education. This is a documental research of qualitative nature, for which we analyzed the formative notebooks of the program used in 2013, focused on the Portuguese Language (beginning literacy, reading and writing). The general aim is to investigate how, in these documents, the theoretical propositions and the reports of successful activities relate literacy and texts. But under the political bias through which it is traversed, this work also covers social relations, historical memories, political-pedagogical perspectives and challenges embedded in the approaches that constitute this material, answering the following research questions: a) What does "literacy writing" or "literacy perspective" mean in the PNAIC' proposals? b) How do the systematic and explicit teaching activities of the writing system associate with the texts? c) What are the influences exerted by traditional approaches in the program? d) How does the program reflect the history of literacy policy in Brazil? The results of the analysis show that the proposal of teaching the writing system from the perspective of literacy, by bringing together textual approach and analysis of linguistic structures, works with these practices within a continuum of pedagogical possibilities, which sometimes integrates or articulates them. They are integrated when, although contemporary in the literacy period, they are developed in parallel, in different didactic moments, to address the respective specificities of these dimensions. When they are articulated, the realization of texts and thinking about language are related simultaneously, happening in the same didactic event, which contributes to the construction of knowledge related to both. There are still challenges to the teaching of the writing system articulated to textual approaches, in order to serve the interaction purposes in communicative situations. However, pedagogically, in view of a history of literacy that has been for a long time inexpressive, the text has gained space in teaching, although it is still little approached under more problematizing and political perspectives. In addition, although there are memories of traditional teaching strategies, there are substantially changes that aim at the formation of students under the premise of reflection, of the construction of knowledge. Specifically in the political field, a historical research of education in the country, from Jesuit education to the institution of the PNAIC, shows us inheritances and permanencies in Brazilian school education. We still have absent and partisan governments, which find in education programs a way of directing blame for school failure to the school itself, ignoring other responsibilities that have an equal impact on educational outcomes. In this scenario, the literacy teacher emerges as a key element in the processes of basic literacy and literacy, being the articulator that will directly enable (or not) more meaningful language practices, which make the school closer to life beyond class. Hence, the importance of the program to the improvement of teacher's work and for changes in teaching.